Design-and-develop approach in the construction of a do-it-yourself microscope enhancing accessibility in Science education - Reyes, Ronald L. (Philippine Journal of Science, 2024)
Laboratory experiments and activities have long been integral to the science curriculum, serving as primary mechanisms for connecting theoretical concepts with the natural world. However, traditional experiments often require a physical laboratory, specialized equipment, strict safety protocols, and the presence of a highly trained instructor. In response to the challenges posed by the recent pandemic and other global educational shifts, this study presents a design-and-develop approach, structured according to the ADDIE (analyze, design, develop, implement, evaluate) model, for assembling a do-it-yourself (DIY) microscope project tailored for introductory science courses. The project emphasizes cost-effective strategies for creating alternative educational science materials that enhance accessibility and empower both learners and educators. The design phase utilized common household and readily available materials, including used plastic pipes and containers, wood, flashlights, and inexpensive magnifier lenses. During the analysis, design, and development phases, prototypes were iteratively refined, followed by rigorous testing and validation to assess the feasibility and effectiveness of the DIY microscopes in educational settings. While the images captured by the student-made microscopes displayed less detail compared to those taken with laboratory-grade optical microscopes, the evaluation phase demonstrated the apparatus’s efficacy in fostering curiosity, promoting experiential learning, and enhancing accessibility in science education. The study underscores the utility of this approach in engaging students in scientific inquiry, thereby reinforcing key aspects of scientific thinking and the overall science learning process.